6p-(5p+5)=7(2x+4)+x

Simple and best practice solution for 6p-(5p+5)=7(2x+4)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p-(5p+5)=7(2x+4)+x equation:


Simplifying
6p + -1(5p + 5) = 7(2x + 4) + x

Reorder the terms:
6p + -1(5 + 5p) = 7(2x + 4) + x
6p + (5 * -1 + 5p * -1) = 7(2x + 4) + x
6p + (-5 + -5p) = 7(2x + 4) + x

Reorder the terms:
-5 + 6p + -5p = 7(2x + 4) + x

Combine like terms: 6p + -5p = 1p
-5 + 1p = 7(2x + 4) + x

Reorder the terms:
-5 + 1p = 7(4 + 2x) + x
-5 + 1p = (4 * 7 + 2x * 7) + x
-5 + 1p = (28 + 14x) + x

Combine like terms: 14x + x = 15x
-5 + 1p = 28 + 15x

Solving
-5 + 1p = 28 + 15x

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 1p = 28 + 5 + 15x

Combine like terms: -5 + 5 = 0
0 + 1p = 28 + 5 + 15x
1p = 28 + 5 + 15x

Combine like terms: 28 + 5 = 33
1p = 33 + 15x

Divide each side by '1'.
p = 33 + 15x

Simplifying
p = 33 + 15x

See similar equations:

| 3x-20=155 | | -5(3+4x)=-75 | | 5-9x=77-30x | | 3x+5-10=3x-5x | | 12w^2-27=0 | | 3x/2+1 | | 2(-4x-7)=50 | | 3x-2(x+7)=m+14 | | 3x+2x=25-5 | | 27x^6+8=35x^3 | | 3x/5+6=4x+8 | | 5(6x+3)=-315 | | (5x+6)^2/3=(9+4x)^2/3 | | 9x-6=50 | | 1/2x-3=-4 | | y/2=8 | | 500x=600x+300 | | 2y-6=-14 | | 84*n=420 | | n/5=73 | | 14*n=42 | | 70=3z+16 | | 64*n=384 | | 9/5(191.8-273.15)+32 | | 7X-3=3X-13 | | n/3=81 | | 87=4x+7 | | n*9=63 | | n/7=21 | | 49=3x+7 | | 5x-7=30 | | 2y+3-3=-28 |

Equations solver categories